High dose botox injection for treatment of high grade vesicoureteral reflux in a complicated pediatric case: A case report - Narjes Saberi; Faezeh Sadat Jandaghi (Urology Case Reports)
Vesicoureteral reflux (VUR) is a medical condition affecting the bladder and kidneys. Management depends on bladder capacity and compliance. This study found that high-dose BoNT-A is effective in managing high-grade VUR in pediatric patients. In our case, a 3-year-old male with sacral agenesis and neurogenic bladder, experienced a decrease in creatinine levels and improved vesicoureteral reflux after 20 units/kg of BoNT-A were injected into the detrusor and about 100 units were injected into the external sphincter at 3, 9, and 6 o'clock positions.